(untitled) (Sebha University Conference Proceedings, 2024)
In the past few years, many countries have seen a significant increase in overall energy demand. Building energy consumption for air conditioning and electric heating represents a remarkably high percentage of total energy consumption in Libya. In addition, high temperatures in the summer lead to a significant increase in energy needs, which in turn depends on building materials used in the building walls. In this study, a simulation was carried out using MATLAB program for seven different types of wall materials available in Sebha city. The residential house with an area of ​​170 m2 in is used as sample in this simulation. In MATLAB, the ASHRAE method is used for calculation of thermal load of house. The wall material used in our simulation includes hollow cement bricks, red bricks, sand bricks, expanded polystyrene (EPS), insulated or double bricks (with air gap), limestone brick, and clay bricks. Thermal loads were calculated using via the MATLAB program over four months, January and December for the heating load and July and August for the cooling load. The study showed that the wall of cement bricks has the highest load of (8.16 kw) at 7 a.m. and the sand has (1.95 kw) at the same time of the heating load in January. The highest cooling load in July was (10.1 kw) for cement bricks at 18 o’clock and at the same time (1.7 kw) for sand bricks. Since Sebha city has high solar radiation during the year, we recommend to use solar energy to supply residential buildings with the energy needed for cooling and heating processes to save energy consumption.